127k views
1 vote
Help please! i really need help, i cant figure it out on edginuity

Help please! i really need help, i cant figure it out on edginuity-example-1

2 Answers

6 votes

Answer:


x = - 6

Explanation:


\sqrt[3]{5x - 4} = \sqrt[3]{7 + 8}


5x - 4 = 7x + 8


5x - 4 - 7x = 8


- 2x - 4 = 8


- 2x + = 8 + 4


- 2x = 12


x = (12)/( - 2)


x = - 6

Hope it is helpful....

User Osi
by
5.5k points
1 vote

Answer:

X=-6

Explanation:

Sorry don't have explanation

User Sirmabus
by
6.0k points